THE IMPACT OF EMOTIONAL INTELLIGENCE, TEACHER-STUDENT RELATIONSHIPS, PARENTAL INVOLVEMENT, AND CLASSROOM CLIMATE ON PRESCHOOLERS' SOCIAL-EMOTIONAL DEVELOPMENT - Iskandar, Yusuf (Proyeksi, 2024)
This research aims to examine the influence of emotional intelligence, teacher-student relationships, parental involvement, and classroom climate on the social-emotional development of Indonesian preschool children in Sukabumi Regency. A total of 80 preschool children and their parents were recruited as participants. Data were collected using a questionnaire and analyzed with SPSS. The results of the study showed that emotional intelligence, teacher-student relationships, parental involvement, and classroom climate have a positive and significant effect on the social-emotional development of Indonesian preschool children. Specifically, higher emotional intelligence, positive teacher-student relationships, greater parental involvement, and a positive classroom climate were associated with better socio-emotional development in preschool children. The findings highlight the importance of focusing on these factors in early childhood education programs to promote the social-emotional development of preschool children in Indonesia.